2007
DOI: 10.1111/j.1582-4934.2007.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of different abzymes in autoimmune‐prone MRL‐lpr/lpr mice is associated with changes in colony formation of haematopoietic progenitors

Abstract: It was shown that IgGs from the sera of 2–7-month-old control non-autoimmune (CBA x C57BL)F1 and BALB/c mice and 2–3-month-old autoimmune prone MRL-lpr/lpr mice (conditionally healthy mice) are catalytically inactive. During spontaneous development of deep systemic lupus erythematosus (SLE)-like pathology a specific reorganization of immune system of these mice leads to conditions associated with a production of IgGs hydrolyzing DNA, ATP and polysaccharides with low catalytic activities (conditionally pre-dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
333
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 57 publications
(347 citation statements)
references
References 49 publications
(100 reference statements)
9
333
0
5
Order By: Relevance
“…The average anti-DNA Abs concentration in the case of (CBAxC57BL)F1 and BALB/c nonautoimmune control mice was estimated to be approximately 0.03-0.04 A 450 units and was comparable with that for healthy autoimmune-prone MRL-lpr/lpr mice (0.032 A 450 units) [29][30][31]. After spontaneous development of SLE in MRL-lpr/lpr mice (depending of individual mice during 4-7 months), it increases to 0.2 A 450 units, but there were no remarkable change in the anti-DNA Abs titers in the case of control nonautoimmune mice during 7-8 months of the experiment [29][30][31].…”
Section: Catalytic Activities Of Sle Prone Mice Antibodiesmentioning
confidence: 81%
See 4 more Smart Citations
“…The average anti-DNA Abs concentration in the case of (CBAxC57BL)F1 and BALB/c nonautoimmune control mice was estimated to be approximately 0.03-0.04 A 450 units and was comparable with that for healthy autoimmune-prone MRL-lpr/lpr mice (0.032 A 450 units) [29][30][31]. After spontaneous development of SLE in MRL-lpr/lpr mice (depending of individual mice during 4-7 months), it increases to 0.2 A 450 units, but there were no remarkable change in the anti-DNA Abs titers in the case of control nonautoimmune mice during 7-8 months of the experiment [29][30][31].…”
Section: Catalytic Activities Of Sle Prone Mice Antibodiesmentioning
confidence: 81%
“…It was shown that abzymes with different activities may be obtained with a significantly higher incidence in autoimmune mouse strains comparing to conventionally used control nonautoimmune mice [51,52]. Immunization of autoimmune-prone MRL-lpr/lpr mice with DNA-protein complexes also results in significantly higher production of anti-DNA Abs and abzymes with DNase activity comparing with nonautoimmune CBA and BALB/c healthy mice [29][30][31]. At the same time, artificial antiidiotypic abzymes can be induced by immunization of animals with different enzymes [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations